2015
DOI: 10.1016/j.jped.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biochemical and immunological profile of pediatric patients with acute myeloid leukemia in relation to healthy individuals

Abstract: It was possible to characterize the biochemical and immunological profile of pediatric patients with AML, as well as highlight some significant differences in these parameters when comparing with healthy children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…[44][45][46] This may explain the fact that PC2 and PC3 exhibit some peaks related to amino acids with higher intensities in the healthy compared to leukemic groups, especially Tyr and Trp. The peaks of proteins and glutathione (linked to erythrocytes) are also found in lower intensities in the leukemic group, which was also observed by Sanches et al, 47 who carried out a study comparing the biochemical profile between leukemic patients and healthy individuals. The peak assigned to the amino acid Phe was highlighted in the first three loadings.…”
Section: Exploratory Analysissupporting
confidence: 79%
“…[44][45][46] This may explain the fact that PC2 and PC3 exhibit some peaks related to amino acids with higher intensities in the healthy compared to leukemic groups, especially Tyr and Trp. The peaks of proteins and glutathione (linked to erythrocytes) are also found in lower intensities in the leukemic group, which was also observed by Sanches et al, 47 who carried out a study comparing the biochemical profile between leukemic patients and healthy individuals. The peak assigned to the amino acid Phe was highlighted in the first three loadings.…”
Section: Exploratory Analysissupporting
confidence: 79%
“…11 Recently, a study of a small pediatric AML cohort showed that IL-6 levels in peripheral blood were elevated compared with healthy age-matched controls. 12 However, the cytokine milieu in the BM niche of pediatric patients with AML has not been investigated previously. This is partially due to a lack of available banked samples.…”
Section: Introductionmentioning
confidence: 99%
“…High serum levels of IL-6 have also been observed in these cancer conditions. In particular, compared to healthy children and adolescents, pediatric patients with acute myeloid leukemia showed higher concentrations of IL-6 and TNFα [ 29 ]. Up-regulation of cytokines in the bone microenvironment may contribute to peripheral and central components of cancer-induced bone pain, as osteoclasts are derived from monocyte/macrophage hematopoietic lineage and express receptors for TNFα and IL-6 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%